1973
DOI: 10.1084/jem.138.3.607
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human B and T Lymphocytes by Scanning Electron Microscopy

Abstract: In this study a variety of human lymphocytes of known B or T cell type, obtained from multiple sources, were prepared for scanning electron microscopy (SEM) by the critical point drying method. Distinction between normal B and T lymphocytes was relatively easy in most instances, on the basis of their surface architecture. Using immunological methods, between 20 and 30% of normal peripheral blood lymphocytes (PBL) were identified as B cells and from 69 to 82% as T cells. SEM results showed that 20% of the PBL h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0
5

Year Published

1974
1974
1979
1979

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(84 citation statements)
references
References 27 publications
8
71
0
5
Order By: Relevance
“…These observations have confirmed by immunologic identification previous observations by scanning electron microscopy (S.E.M.) of Polliack and CO-workers (4).…”
Section: Introductionsupporting
confidence: 79%
“…These observations have confirmed by immunologic identification previous observations by scanning electron microscopy (S.E.M.) of Polliack and CO-workers (4).…”
Section: Introductionsupporting
confidence: 79%
“…Recently, T and B lymphocytes have become identifiable on the basis of their surface structure by the scanning electron microscope (POLLIACK et al, 1973(POLLIACK et al, , 1975LIN et al, 1973). Many works suggest that T lymphocytes form the great majority of recirculating cells which may enter from blood to lymph via the postcapillary wall of these vessels should be T lymphocytes.…”
mentioning
confidence: 99%
“…Since LIN et al (1973) and POLLIACK et al (1973) reported "smooth" T cells and "hairy" B cells by scanning electron microscopy, many conflicting reports have been published on the surface morphology of T and B lymphocytes. At the present, the most acceptable view seems that any differences seen in scanning electron micrographs are probably due either to the functional state of the lymphocyte, or to its place in the differentiation pathway, or its response to environment during process-ing (ROATH et al, 1978).…”
Section: Discussionmentioning
confidence: 99%